Tumor markers in the treatment of patients with gastric cancer - A. F. Chernousov; T. V. Khorobrykh; I. I. Bykov; M. V. Nemtsov; A. A. Udilova; A. B. Bekshokov (Сеченовский вестник)
The article presents the results of many years work carried out at the Department of Surgery of the I.M. Sechenov First MSMU in one of the priority areas — the study of molecular-genetic markers. The possibilities of use of the molecular-genetic markers in treatment of gastric cancer patients are discussed.